Factors Associated with Utilization Triple Elimination Examination by Pregnant Women In Indonesia: Scoping Review - Yulfiana; Chriswardani Suryawati; Ayun Sriatmi (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: The prevalence of HIV, Syphilis and Hepatitis B infections among pregnant women in Indonesia has reached 0.3%, 1.7% and 2.5%, respectively. The risk of transmission from mother to child respectively 20%-45%, 69-80% and more than 90%. Transmission of these three diseases from pregnant women to babies during pregnancy, childbirth and breastfeeding cause disabilities in children and even death. The government stipulates that all pregnant women are required to HIV/AIDS, Syphilis and Hepatitis B screening (Triple elimination examination) at integrated antenatal services. The target set is that early detection of HIV, syphilis and hepatitis B in pregnant women must reach 100% through examinations at First Level Health Facilities and Referral Health Facilities by 2022. However, in 2021 the achievements were only 50.8%, 16.4% and 60.3% for HIV, syphilis and hepatitis B. Objective: This study aims to determine the factors associated with the utilization of triple elimination examinations by pregnant women. Method: This study uses a scoping review method. Article collected from online databases including scopus, science direct, proquest, EBSCO, PupMed and Google Scholar with keywords